Incident infection risks depending on oral antidiabetic exposure in insulin-treated type 2 diabetes patients - Park, Sanghwa; Jeong, Jiseon; Woo, Yunna; Choi, Yeo Jin; Shin, Sooyoung (Scientific Reports, 2023)
Dipeptidyl peptidase-4 inhibitors (DPP4is) and sodium glucose cotransporter-2 inhibitors (SGLT2is) have been speculated to have a potential to increase infection risks in type 2 diabetes mellitus (T2DM) patients. We performed a cohort study using the Korean health insurance data to investigate infection risks with each drug class relative to metformin in insulin-treated T2DM patients. After propensity score matching, we included 1,498 and 749 patients in DPP4i + insulin vs metformin + insulin and 300 and 549 patients in SGLT2i + insulin vs metformin + insulin, respectively. In stratified analyses per patient factor, none of the odds ratios (ORs) were associated with a statistical significance across respiratory, genital, and urinary tract infections (UTIs), except that of the male stratum for respiratory infections (OR 0.77, p = 0.04). With regard to SGLT2is, a higher risk of genital infections was analyzed with their use than with metformin therapy (OR 1.76, p = 0.03). In stratified analyses, the OR for genital infections remained significant in the baseline cardiovascular disease stratum (OR 2.29, p = 0.01). No increased UTI risk was detected with SGLT2is compared against metformin. In this study on insulin-receiving T2DM patients, DPP4is were not associated with increased infection risks, whereas SGLT2is led to a higher risk for genital infections, but not for UTIs, relative to metformin.
Keywords: Cohort Studies; Diabetes Mellitus, Type 2; Dipeptidyl-Peptidase IV Inhibitors; Humans; Hypoglycemic Agents; Insulin; Male; Metformin; Retrospective Studies; Urinary Tract Infections